PEMANFAATAN TEKNOLOGI ARTIFICIAL INTELLIGENCE DALAM MENUNJANG EFEKTIVITAS PEMBELAJARAN MAHASISWA UNIVERSITAS NUSA CENDANA DI ERA SOCIETY 5.0 - Ayu Fitriani Rizkiyah Lestari; Arini Rahma Dhani (Universitas Nusa Cendana, 2025)
This study examines the role of Artificial Intelligence (AI) technology in supporting the learning effectiveness of students at the University of Nusa Cendana in the Society 5.0 era. The background of this research is based on the importance of integrating intelligent technologies into higher education to create learning that is more adaptive, effective, and personalized. The purpose of this study is to determine the extent to which AI is used by students and how it impacts learning effectiveness. The method employed is descriptive quantitative, with data collected through an online questionnaire involving 76 active students. Data analysis was conducted using descriptive statistics to identify usage patterns and students' perceptions of AI. The results show that 98.7% of students have used AI, with 38.2% using it daily and 53.9% several times a week. These findings conclude that AI is a beneficial learning tool, but not a substitute for educators